Experimental Study on Microbial Concentration Optimization in Cement Mortar using M-Sand as Fine Aggregate. Issue 1 (September 2020) - Benjamin, Babitha; Sabbavarapu, Anisha; Sudhakumar, J; Suchithra, T V
Abstract: One of the major shortcomings of conventional concrete based constructions is its gradual strength deterioration over time due to its week tensile strength. Without any effective measures to remedy this problem the alternatives we have now are periodic monitoring, retrofitting, repair & rehabilitation, etc. The above-mentioned methods are all highly unsustainable due to manpower, money and materials being spend in a cycle to upkeep. If a protective coating of microbial cement mortar is given to the structures like bridges, underground tunnels, etc. were a lot of dampness is observed, structural deterioration can be prevented. The study is aimed at optimizing the concentration of bacteria in self-healing cement mortar which uses microbiologically induced calcium carbonate precipitate to induce crack healing ability. For this purpose, bacteria Bacillus Subtilis MTCC441 (non-ureolytic) were added in concentrations 10 4, 10 6, 10 8 cells/ml to a mix using M-sand as fine aggregate. The bacteria were cultured in a nutrient broth and were added to cement mortar by water medium during mixing. The addition to cement mortar was done when the microorganisms were still alive and active. In this study, a series of experiments like compressive strength, water absorption, and pour healing was done to optimise the concentration. The results showed that 10 6 cells/ml was the optimum quantity of microorganisms required to enhance the physical properties of concrete.